TECHNOLOGIES FOR TEACHING LEXICAL CONCEPTS THROUGH DICTIONARY WORK (ResearchJet Journal of Analysis and Inventions, 2021)
The native language and literature of any nation is its national spirit and identity.The cultural and enlightenment world is the basis of the national idea.The wise words of our enlightened ancestor Abdullah Avloni,’’The mirror life of every nation is the language and literature that shov its existence in the world.To lose the national language is to lose the spirit of the nation,”confirm this idea.This article discusses modern pedagogical technologies,vocababulary in the primary school ,working on vocabulary in the primary school,content,essence,form,method and various modern pedagogical technologies.